RESEPSI KOVER NOVEL CANTIK ITU LUKA (2015) DALAM VERSI TERJEMAHAN BAHASA INGGRIS - Sari, Mustika Wulan; Arofani, Nilam Yuhanisa; Susanto, Dwi (Widyaparwa, 2023)
The novel Beauty Is a Wound is an English translation of the original Cantik Itu Luka by Eka Kurniawan. These two novels have two different covers due to the reception they received from the publishers. This study aims to examine the cover reception of Beauty Is a Wound. This paper also looks at the differences in visual design between the two novels and examines how the publisher gave its reception through the cover of Beauty Is a Wound. The qualitative research method prioritizes data quality. Data collection is done by observing, reading, and taking notes. The research data covers of Cantik Itu Luka (2015) and Beauty Is a Wound (2015), texts related to novels, authors, and publishers, as well as information about literary receptions. Data were analyzed through data reduction, presentation, and interpretation. The results of this study reveal that the reception on the cover of Beauty Is a Wound occurs due to readers having different social and cultural backgrounds. In addition, market tastes are also an essential consideration for publishers to provide their responses. Novel Beauty Is a Wound merupakan terjemahan bahasa Inggris dari versi original Cantik itu Luka karya Eka Kurniawan. Kedua novel ini memiliki dua kover berbeda karena munculnya resepsi oleh penerbit. Penelitian ini bertujuan mengkaji resepsi kover Beauty Is a Wound. Tulisan ini juga melihat perbedaan desain visual antara kedua novel tersebut, dan mengkaji bagaimana penerbit memberikan resepsinya melalui kover Beauty Is a Wound. Metode penelitian berjenis kualitatif mengutamakan kualitas data. Pengumpulan data dilakukan dengan mengamati, membaca, dan mencatat. Data penelitian berupa kover Cantik Itu Luka (2015) dan Beauty Is a Wound (2015), teks-teks terkait novel, pengarang, dan penerbit, serta informasi-informasi tentang resepsi sastra. Data dianalisis melalui reduksi data, menyajikan data, dan interpretasi data. Hasil penelitian ini mengungkapkan resepsi dalam kover Beauty Is a Wound terjadi akibat dari pembaca yang memiliki latar belakang sosial dan budaya yang berbeda. Selain itu, selera pasar juga menjadi pertimbangan penting terhadap penerbit untuk memberikan tanggapannya.